SMART BUSINESS PROCESS AUTOMATION: STRATEGIC ADVANTAGES, CHALLENGES, AND RISK MITIGATION APPROACHES - Doniyor Umarov (Modern American Journals, 2025)
This article investigates business process automation (BPA) as a strategic instrument for enhancing organizational efficiency and adaptability in the context of global digital transformation. The work presents a comprehensive and analytical evaluation of the opportunities offered by automation—including improved productivity, operational standardization, and cost efficiency—alongside the risks and limitations that accompany large-scale implementation, such as technical failures, social resistance, and loss of flexibility. Particular attention is given to the role of human capital, organizational culture, and technological integration in achieving sustainable results. Drawing on recent empirical studies and cross-industry examples, the article argues for a systemic, balanced, and ethically informed approach to automation. The insights provided can support the design of digital transformation strategies and inform policy and management decisions aimed at increasing enterprise resilience and competitiveness.